Stability and Yielding Performance of Seven Chickpea Genotypes (Cicer Arietinum L.) Over a Range of Environments in Sulaimani, Iraq - Hamma-Umin, Bestoon Omar (Sulaimani Journal for Pure and Applied Sciences, 2019)
Seven genotypes of Chickpea (Cicer arietinum L.), namely; FLIP 97-706C, FLIP 03-87C, FLIP 05-74C, FLIP 05-87C, FLIP 05-110C, FLIP 05-142C, and FLIP 05-150C were evaluated in three different environments in Sulaimani-Qlyasan during every spring from 2016 until 2018.Using Randomized Completely Block Design (RCBD) with three replications in order to study the stability and genotypic resultant growth and yieldcharacters. The results exhibited highly significant effects due to genotypes ×seasons in most of the studied characters with the exception of no. of seeds/pod and no. of branches/plant. The genotype (FLIP 05-150C) was considered the best genotype, which had the high homeostasis values for six characters plant height (0.984), plant weight (0.954), no. of pods/plant (0.951), no. of seeds/plod (0.977), 100 seed weight (0.973) and seed weight/plant(0.930). This genotype needs to be assessed in more varied environments examine. The highest genotypic resultant values were recorded by the genotype (FLIP 05-150C) for plant height (1.109), plant weight (1.020), no. of pods/plant (1.427), no. of seeds/pod (1.001), 100 seed weight (1.095) and seed weight/plant (1.150), indicating this genotype had high performance at different environments and should be not disregarded in future studies.
Keywords: Chickpea; Stability; Homeostasis; Genotypic Resultant Analysis; Genotype Environment